Changes in multimorbidity burden over a 3–5 year period among people with HIV - Sukumaran, Luxsena; De Francesco, Davide; Winston, Alan; Mallon, Patrick W. G.; Doyle, Nicki; Anderson, Jane; Boffito, Marta; Williams, Ian; Post, Frank A.; Vera, Jaime; Sachikonye, Memory; Johnson, Margaret A.; et al. (Frontiers in Systems Biology, 2023)
Introduction: As people living with HIV age, the increasing burden of multimorbidity poses a significant health challenge. The aims of this study were to identify common patterns of multimorbidity and examine changes in their burden, as well as their associations with risk factors, over a 3–5 year period in people with HIV, enrolled in the Pharmacokinetic and clinical Observations in PeoPle over fiftY (POPPY) study. Methods: Common multimorbidity patterns were identified in POPPY participants with HIV using principal component analysis, based on Somers’ D statistic. Multimorbidity burden scores were calculated for each participant/pattern at study entry/follow-up and were standardised relative to the mean in the sample at baseline (scores >0 thus reflect a greater number of comorbidities relative to the mean). Two multivariable linear regression models were fitted to examine the associations between risk factors and burden z-scores at baseline and change in z-scores over a 3–5 year period. Results: Five patterns were identified among the 1073 POPPY participants with HIV median age [interquartile range (IQR)], 52 (47–59) years; 85% male and 84% white: Cardiovascular diseases (CVDs), Sexually transmitted diseases (STDs), Neurometabolic, Cancer and Mental-gastro-joint. The multivariable linear regression showed that older age, behavioural factors (i.e., body mass index (BMI), history of injection drug use, current recreational drug use and sex between men), and HIV-specific factors (i.e., duration since HIV diagnosis and a prior AIDS diagnosis) were associated with higher multimorbidity burden at baseline. However, only three of the factors (age, BMI and duration since HIV diagnosis) were significantly associated with an increase in burden across specific patterns over time. Discussion: Key modifiable and non-modifiable factors contributing to an increase in burden of multimorbidity were identified. Our findings may inform the development of more targeted interventions and guidelines to effectively prevent and manage the rising burden of multimorbidity in people with HIV.